New Ways of Working in the Manufacturing Sector as COVID-19 Pandemic Learning and Its Relevance to Workforce Agility - Fransiska Cicilia Pembayun Noviansista Cornelis; Hary Febriansyah (Research Synergy Foundation, 2023)
The performance of manufacturing as the prominent sector decreased because of the COVID-19 pandemic. Nevertheless, it could bounce back its performance quickly right after. The question remains whether new ways of working take part in this agile behavior of manufacturing employees in adapting to such a situation. Even so, what kind of new ways of working could be implemented in manufacturing since this sector has a specific processing system from input to output? Implementing new ways of working practices in manufacturing varies since manufacturing has primary and support activities. First, this paper elaborates on the definition of new ways of working and the feasible practices that could be implemented in manufacturing. They are ICT, flexible work time, flexible workplace, and professional autonomy. Second, this paper uses the triadic reciprocal of social cognitive theory to find the relevance of new ways of working and workforce agility. Furthermore, psychological empowerment plays an important part in implementing new ways of working regarding employee sustainability as a human being who needs intrinsic motivation. The authors conclude with the proposed model that depicts the relevance between new ways of working practices, psychological empowerment, and workforce agility. This study also provides managerial implications in implementing new ways of working in the manufacturing sector.